The assertion of fundamental principles relating to civil law notaries in the 21st century with special focus on Hungary - Molnár, Tamás (Pro Futuro, 2020)
Jelen tanulmányban a magyar közjegyzőség elemzésén keresztül teszünk kísérletet a közjegyzőségre vonatkozó egyes alapelvek bemutatására. Az első fejezetben a magyar közjegyzőségre vonatkozó általános szabályok kerültek bemutatásra, köztük a magyar közjegyző jogállása. Ezt követően a közjegyzői eljárások csoportosítása és bizonyos szervezeti jellemzők értékelését kíséreljük meg. Ezzel kapcsolatban taglaljuk, hogy nem kizárólag okirat-szerkesztési, hanem regisztrációs eljárások is a magyar közjegyző hatáskörébe tartoznak. A tanulmányban a közjegyzők felelőssége, reklámra vonatkozó tevékenysége, valamint az elektronizáció és a digitalizáció számos kérdése is elemzésre kerül. A tanulmány bemutatja továbbá a közjegyzőkre vonatkozó legfontosabb alapelveket, köztük a függetlenség, pártatlanság és a közhitelesség elvét.In our present paper, we tried to introduce the principles of notaries through the Hungarian notary's glasses. We did this through the challenges of the 21st century. Prior to the detailed description of the principles, we introduced the position of the Hungarian notary, where we also discussed the provisions of the Hungarian Constitution. Subsequently, more important legislation on Hungarian notary was mentioned and we discussed the diverse notarial procedures. In this connection, it is important to note that not only the notarial deeds are found in the Hungarian notary's procedures, but also the keeping of notarial registers. The paper deals with the responsibility of notary, the notary's and advertising relationships, the emergence of electronization and digitization. The paper presents the most important principles of notaries, including the principle of independence, impartiality and public authenticity.